Young adults with substance use disorders have unique treatment requirements. Issue 3 (3rd February 2021) - Knopf, Alison
Abstract : Researchers at the Grayken Center for Addiction at Boston Medical Center have published principles of care for young adults with substance use disorder (SUD), recognizing that this age group has unique requirements.